(untitled) (Mustansiria Dental Journal, 2018)
A successful endodontic treatment requires that the apex of the treated tooth be completely and densely sealed with root canal filling material. One of the most difficult endodontic problems is the management of necrotic immature tooth due to the blunderbuss apex and the difficulty in achieving a tight seal between the root canal system and the external surface of the tooth. The aim of this study was to evaluate the sealing ability the apical calcified bridge formed by calcium hydroxide paste, white MTA or gray MTA during apexification procedure. Thirty premolars with single root canals were prepared to simulate an open apex. These roots were divided into 3 groups as follow: Group A: 10 roots filled with Ca(OH)2 paste, Group B: 10 roots filled with white MTA, and Group C: 10 roots filled with gray MTA. Each root was placed in a polyethylene vial containing 25 m1 of synthetic tissue fluid (STF) and incubated at 37°C for 3 months. After 3 months and the formation of calcified bridge, each root was immersed in 2% freshly prepared Methylene blue dye in 5 ml plastic vial for seven days. After the leakage period, the roots were removed from the dye and the leakage in all roots was examined by measuring the linear extent of dye penetration from the apical end of the canal preparation to the coronal direction by means of a light stereomicroscope at (40 X) magnification with calibrated grid. Ca(OH)2 paste group has the highest mean value of apical dye penetration followed by WMTA, while GMTA group shows the lowest mean value of apical dye penetration. There was a highly significant difference in the apical dye penetration (p<0.01) among these groups, statistically a high significant difference is found (p<0.01) between Ca(OH)2 group and WMTA group, and between Ca(OH)2 group and GMTA group; whereas, significant difference is found (p<0.05) between WMTA group and GMTA group. The apical calcified bridge formed by GMTA has the best sealing ability followed by that formed by WMTA. While the apical calcified bridge formed by Ca(OH)2 paste has the lowest sealing ability as compared with that formed byWMTA and GMTA.